Mental health literacy among primary care providers in Hungary: a vignette-based survey - Valerie S. Swisher; Dorottya Őri; Zoltán Rihmer; Róbert Wernigg (Annals of General Psychiatry)
Abstract Objective This study examined mental health literacy and predictors of disorder recognition among primary care providers (PCPs) in Hungary. Methods 208 PCPs in Hungary completed a survey assessing demographics, mental health stigma, and exposure to mental health (i.e., personal experiences and having a family member/friend with a mental health condition). Participants read six vignettes describing obsessive-compulsive disorder (OCD) harm/aggression subtype (OCD-Aggression), OCD order/symmetry subtype (OCD-Order), generalized anxiety disorder (GAD), social anxiety disorder (SAD), panic disorder (PD), and major depressive disorder (MDD) and were asked to identify each condition, perceived disorder causes, and provide treatment referrals. Descriptive analyses were used to characterize disorder recognition rates, perceived disorder causes, and treatment referrals. Binary logistic regression analyses were conducted to examine the degree to which demographic characteristics, mental health stigma, and exposure to mental health conditions predict accurate disorder recognition. Results Identification rates for each vignette were: OCD-Aggression (27.9%), OCD-Order (75.5%), SAD (34.1%), GAD (76.0%), PD (78.8%), and MDD (91.3%). First-choice treatment referrals were a psychiatrist for OCD-Aggression (63.0%), OCD-Order (53.8%), and MDD (46.6%), a psychologist/therapist for SAD (58.7%) and GAD (48.6%), and a PCP for PD (39.9%). Mislabeling conditions was significantly associated with older age (for GAD, OCD-Aggression, PD and MDD), male gender (for GAD), greater mental health stigma (for OCD-Order), and lack of exposure to mental health conditions (for SAD). Conclusions Findings highlight strengths (e.g., depression recognition) and limitations in knowledge of mental health conditions among PCPs in Hungary and identifies targets to address to improve mental health literacy.